2019
DOI: 10.1186/s13073-019-0666-2
|View full text |Cite
|
Sign up to set email alerts
|

Best practices for bioinformatic characterization of neoantigens for clinical utility

Abstract: Neoantigens are newly formed peptides created from somatic mutations that are capable of inducing tumor-specific T cell recognition. Recently, researchers and clinicians have leveraged next generation sequencing technologies to identify neoantigens and to create personalized immunotherapies for cancer treatment. To create a personalized cancer vaccine, neoantigens must be computationally predicted from matched tumor–normal sequencing data, and then ranked according to their predicted capability in stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
151
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 210 publications
(230 reference statements)
2
151
0
Order By: Relevance
“…Several highly immunogenic TSAs have already been described [260][261][262][263]. However, modern methods such as high-throughput sequencing technologies and bioinformatics analysis of big data allow the identification of new tumor antigenic determinants, such as neoantigens [264,265]. This makes it possible to analyze and determine the TSAs specifically expressed by each cancer patient's tumor, with further TSA or recombinant production and utilization of its peptide in the vaccines that target DCs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Several highly immunogenic TSAs have already been described [260][261][262][263]. However, modern methods such as high-throughput sequencing technologies and bioinformatics analysis of big data allow the identification of new tumor antigenic determinants, such as neoantigens [264,265]. This makes it possible to analyze and determine the TSAs specifically expressed by each cancer patient's tumor, with further TSA or recombinant production and utilization of its peptide in the vaccines that target DCs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Due to high throughput sequencing techniques which enable genome wide detection of genetic variants, bioinformatic pipelines have been developed to predict neoantigens (32)(33)(34)(35) and minor histocompatibility antigens (31,(36)(37)(38)(39)(40). Based on whole exome sequence data, Koparde et al (39) found an average of 2463 non-synonymous SNP disparities in the Graft-versus-Host direction in patients transplanted with related donors, and an average of 4287 SNP disparities in patients transplanted with unrelated donors (39).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, peptide prediction algorithms use either solely the data generated by mass spectrometry (MS) analysis of eluted MHC-binding peptides or both in vitro MHC-peptide binding affinity and MS peptidome data [109][110][111].…”
Section: Selection Of Neoantigen-specific T Cells From the Tumourmentioning
confidence: 99%